Transformation of Learning Technology in Community Learning Centers in the Era of Industry 4.0 Revolution (Sainteknol : Jurnal Sains dan Teknologi, 2022)
Technological developments are developing very rapidly along with the times. The conditions of the Covid pandemic that occurred also contributed to the process of developing technology used by the community. Likewise in terms of education The rapid development of information technology has an impact on the teaching and learning process which requires educational institutions to also use technology as a teaching and learning process in order to improve the quality of education according to what is to be achieved in improving the quality of education non-formal educational institutions must also be willing to transform the teaching and learning process as a whole. conventional towards a technology-based teaching and learning process. as well as a shift in the curriculum that is currently used is an independent curriculum, the learning process focuses on the competence and character of students as well as a flexible learning process in the sense of freeing tutors and students. The purpose of this study was to find out the transformation of learning technology in community educational institutions in the industrial era 4.0 in Tasikmalaya City. The research method used is qualitative research with data collection techniques of interviews, observation and documentation. The results of the research to be achieved are changes in the teaching and learning process that have been carried out by community education institutions so that it can make it easier for students to follow the learning process and can be applied when students graduate later, the transformation of the use of technology in the learning process can also improve the quality of education